Structural control of the non-ionic surfactant alcohol ethoxylates (AEOs) on transport in natural soils. (15th January 2021) - Espeso, M. Botella; Corada-Fernández, C.; García-Delgado, M.; Candela, L.; González-Mazo, E.; Lara-Martín, P.A.; Jiménez-Martínez, J.
Abstract: Surfactants, after use, enter the environment through diffuse and point sources such as irrigation with treated and non-treated waste water and urban and industrial wastewater discharges. For the group of non-ionic synthetic surfactant alcohol ethoxylates (AEOs), most of the available information is restricted to the levels and fate in aquatic systems, whereas current knowledge of their behavior in soils is very limited. Here we characterize the behavior of different homologs (C12–C18) and ethoxymers (EO3, EO6, and EO8) of the AEOs through batch experiments and under unsaturated flow conditions during infiltration experiments. Experiments used two different agricultural soils from a region irrigated with reclaimed water (Guadalete River basin, SW Spain). In parallel, water flow and chemical transport were modelled using the HYDRUS-1D software package, calibrated using the infiltration experimental data. Estimates of water flow and reactive transport of all surfactants were in good agreement between infiltration experiments and simulations. The sorption process followed a Freundlich isotherm for most of the target compounds. A systematic comparison between sorption data obtained from batch and infiltration experiments revealed that the sorption coefficient ( K d ) was generally lower in infiltration experiments, performed under environmental flow conditions, than in batch experiments in the absence of flow, whereas the exponent ( β ) did not show significant differences. For the low clay and organic carbon content of the soils used, no clear dependence of K d on them was observed. Our work thus highlights the need to use reactive transport parameterization inferred under realistic conditions to assess the risk associated with alcohol ethoxylates in subsurface environments. Graphical abstract: Image 1 Highlights: Sorption coefficients were lower and with less variability in infiltration than batch. Similar behavior in natural systems between homologs and between ethoxymers. No dependence of sorption coefficient on low clay and organic carbon content.